Planform Change and Its Delayed Response to Discharge in an Active Braided River Reach: Majuli Island Reach of the Brahmaputra River - Qiange Xue; Li He; Qiuhong Tang; Ximeng Xu; Dong Chen; Nigel G. Wright; G. M. Tarekul Islam; Binod Baniya; A. K. M. Saiful Islam; Ahmed Ishtiaque Amin Chowdhury; Yaoying Tang (Remote Sensing)
As the threat of unstable braided river geomorphology to the resilience of local communities grows, a better understanding of the morphological changes in a river subject to climate is essential. However, little research has focused on the long-term planform change of the braided reaches and its response to hydrological changes. The reach around Majuli Island (Majuli Reach), the first and typical braided reach of the Brahmaputra River emerging from the gorge, experiences intense geomorphological change of the channels and loss of riparian area every year due to the seasonal hydrological variability. Therefore, focusing on the Majuli Reach, we quantitatively investigate changes in its planform morphology from 1990 to 2020 using remote sensing images from the Landsat dataset and analyze the influence of discharge in previous years on channel braiding. The study shows that the Majuli Reach is characterized by a high braiding degree with an average Modified Plan Form Index (MPFI) of 4.39, an average reach width of 5.58 km, and the development of densely migrating bars and active braided channels. Analysis shows a control point near Borboka Pathar with little morphological change, and the braided channel shows contrasting morphological changes in the braiding degree, bars, and main channel between the reach upstream and downstream of it. The area of the riparian zone of the Majuli Reach decreased by more than 50 km2 during the study period due to migration of the main channel toward the island. The braiding degree of Majuli Reach is positively correlated with the discharge in previous years, with the delayed response time of the MPFI to discharge being just 3–4 years, indicating the unstable feature of the Majuli Reach with varied hydrology conditions.